Resting-state electroencephalographic characteristics related to mild cognitive impairments - Kim, Seong-Eun; Shin, Chanwoo; Yim, Junyeop; Seo, Kyoungwon; Ryu, Hokyoung; Choi, Hojin; Park, Jinseok; Min, Byoung-Kyong (Frontiers in Psychiatry, 2023)
Alzheimer's disease (AD) causes a rapid deterioration in cognitive and physical functions, including problem-solving, memory, language, and daily activities. Mild cognitive impairment (MCI) is considered a risk factor for AD, and early diagnosis and treatment of MCI may help slow the progression of AD. Electroencephalography (EEG) analysis has become an increasingly popular tool for developing biomarkers for MCI and AD diagnosis. Compared with healthy elderly, patients with AD showed very clear differences in EEG patterns, but it is inconclusive for MCI.This study aimed to investigate the resting-state EEG features of individuals with MCI (n = 12) and cognitively healthy controls (HC) (n = 13) with eye-closed. EEG data were analyzed using spectral power, complexity, functional connectivity, and graph analysis. The results revealed no significant difference in EEG spectral power between the HC and MCI groups. However, we observed significant changes in brain complexity and networks in individuals with MCI compared with HC. Patients with MCI exhibited lower complexity in the middle temporal lobe, lower global efficiency in theta and alpha bands, lower nodal efficiency in the frontal theta band, and less small-world network topology compared to the HC group. These observed differences may be 1 Kim et al. rsEEG Characteristics for MCI related to underlying neuropathological alterations associated with MCI progression. The findings highlight the potential of network analysis as a promising tool for the diagnosis of MCI.